Analysis of Principal’s Leadership at Unesa Lab School - Widya Nusantara; MV. Roesminingsih; Monica Widyaswari (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
Principals have an essential role in realizing schools that excel, excel, and even. A school principal's ability is not only in carrying out his role as a leader and manager but also, more importantly, as a motivator, innovator, and supervisor, including the principal in the Unesa Lab School Environment. This study aims to analyze the performance of school principals in carrying out their functions as innovators, motivators, and supervisors. The research method uses descriptive quantitative. Research respondents included school principals and educators at Lab school Unesa Junior High School (JHS) 1, Unesa Lab school JHS 2, and Unesa Lab school Unesa Lab school JHS 3. The analysis technique used percentages. The results of this study indicate that the principal's leadership is carried out optimally. The data shows that the principal of Unesa Lab school JHS 1 has a score of 4.31, Unesa Lab school JHS 2 has a score of 4.30, and Unesa Lab school JHS 3 has a score of 4.55. In general, the principal's leadership in carrying out the functions of innovator, motivator, and supervisor has been excellent, and this must be maintained and even improved. For this reason, the principal must have the ability to receive and provide information to subordinates and their environment. As innovators, Principals have tips for establishing a harmonious relationship with a new climate of ideas, and they must also be able to integrate every activity. In carrying out his function as a motivator, the principal must be able to encourage a strong will and will with enthusiasm and confidence for teachers, staff, and students in carrying out their respective duties. The principal's supervisory function can be seen in composing and implementing educational supervision programs and taking advantage of the results.